Kolaborasi Kreatif Manusia dan Ai Untuk Generasi Masa Depan - R. Yadi Rakhman Alamsyah; Reni Nursyanti; Anggi Dewi Nurcahyani (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2026)
Digital transformation is currently dominated by developments in Artificial Intelligence (AI), which are bringing fundamental changes to the creative industry. For today’s youth, particularly vocational high school (SMK) students, mastering AI is no longer just an option but a necessity to maintain relevance and competence in the future.This Community Service Program (PkM) aims to equip students of SMK Bakti Nusantara 666 with a deep understanding of the creative collaboration between humans and AI. Through methods including counseling, practical mentoring in prompt engineering techniques, and evaluations via pre-tests and post-tests, this program targets an 80% increase in participants' digital literacy.The primary focus of this activity is to position AI as an 'intelligent assistant' that expands the imagination without eliminating the originality of human ideas, while consistently upholding ethics and copyright. The results of this program are expected to produce digital talents who are innovative, responsible, and ready to contribute to the creative economy.